Set-up and Calibration by Experimental Data of a Numerical Model for the Estimation of Solar Factor and Ug-value of Building Integrated Photovoltaic Systems. (November 2015) - Mazzali, U.; Ruggeri, P.; Zinzi, M.; Peron, F.; Romagnoni, P.; Daneo, A.
Abstract: The acronym BIPV (Building Integrated Photovoltaics) refers to the installation of photovoltaic systems which, in addition to convert solar energy into electrical energy, have a high level of architectonical integration with the built environment, becoming a real architectural cladding to be installed over the buildings in place of traditional envelope systems. Many typologies of BIPV have been developed, however their thermal characteristics such as g and Ug-value are not well evaluated and require more detailed analyses considering that they could replace large extension of traditional building envelope. A first approach to address this problem is proposed in this work. A mathematical model based on a finite differences scheme for the estimation of the thermal parameters g and Ug-value has been developed and tuned using experimental value measured on sample BIPV with a Hot Plate and a Solar Calorimeter. The results of the model show that the introduction of solar cells in a laminated glass or in a double glass leads to a reduction of energy parameters modifying winter and summer energy balance of the building system.